2003
DOI: 10.1212/01.wnl.0000094357.10782.f9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human herpesvirus-6 in mesial temporal lobe epilepsy surgical brain resections

Abstract: Background-Human herpesvirus-6 (HHV-6), a ubiquitous β-herpesvirus, is the causative agent of roseola infantum and has been associated with a number of neurologic disorders including seizures, encephalitis/meningitis, and multiple sclerosis. Although the role of HHV-6 in human CNS disease remains to be fully defined, a number of studies have suggested that the CNS can be a site for persistent HHV-6 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(208 citation statements)
references
References 46 publications
9
187
1
11
Order By: Relevance
“…Arguments against this hypothesis have been suggested by a recent report demonstrating the presence of active HHV-6 infection in the absence of inflammation in brain samples from a subset of patients with mesial temporal lobe epilepsy (14). Importantly, this study demonstrated the presence of HHV-6-infected astrocytes, supporting the assumption that resident glial cells and not only peripheral lymphocytes leaking through the blood brain barrier might harbor the virus.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Arguments against this hypothesis have been suggested by a recent report demonstrating the presence of active HHV-6 infection in the absence of inflammation in brain samples from a subset of patients with mesial temporal lobe epilepsy (14). Importantly, this study demonstrated the presence of HHV-6-infected astrocytes, supporting the assumption that resident glial cells and not only peripheral lymphocytes leaking through the blood brain barrier might harbor the virus.…”
supporting
confidence: 75%
“…The primers and probes used (Applied Biosystems, Foster City, CA) were specific for the immediate-early region of variants A and B (25). Samples were also quantitatively titrated for human genomic ␤-actin DNA on a third real-time PCR assay, and final viral DNA load per 10 6 cells was calculated by the following formula: (HHV-6 DNA copy number/␤-actin DNA copy number/2) ϫ 10 6 ϭ HHV-6 DNA copy number/ 10 6 cells (14). Results were plotted and sorted using the Sequence Detector System program (Perkin-Elmer, Wellesley, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, CNS infections by HHV-6 lead to benign viral latency, a strategy for persistence used by all members of the herpesvirus family. HHV-6 has been recently demonstrated to infect primary human oligodendrocytes in vitro and in vivo (Albright et al, 1998;Mock et al, 1999;Blumberg et al, 2000;Goodman et al, 2003), as well as human astrocytes (He et al, 1996;Donati et al, 2003), but virtually nothing is known about its effects on glial precursor cells, from which both oligodendrocytes and astrocytes originate.…”
Section: Introductionmentioning
confidence: 99%
“…Several PCR studies of tissue removed during temporal lobectomy from patients with mesial temporal lobe epilepsy have examined the potential etiologic role of HHV6 (47)(48)(49)(50)(51)(52). Results have been variable (Table 2).…”
Section: Human Herpes Virus 6bmentioning
confidence: 99%